Nostos, Nostalgia and Italian Migration - Sturino, Franc (Italian Canadiana, 2021)
The Italian immigrant experience in North America is discussed in relation to the concepts of nostos and nostalgia. The first term, normally referring to the return home from a sea voyage, is discussed comparing the foundational account of nostos, the Odyssey, with the early sojourn phase of Italian migration. By comparison, nostalgia, which can take the form either of homesickness or a longing for the past, is found in the permanent settlement phase, wherein the sense of homesickness predominates pre-World War II while that of longing for the past best defines the post-war period.